ANALISA DAN PERANCANGAN SISTEM INFORMASI ENKRIPSI DATA DENGAN ALGORITMA VIGENERE CHIPER BERBASIS WEB - Makin, Samsul; Rindiansyah, Dodi; Kurniawan, Muhammad Arif; Yuniarti, Angger Styo; Rukmana, Andi (Universitas Insan Pembangunan Indonesia, 2024)
Cryptography is a field of knowledge that uses mathematical equations to perform encryption and decryption processes. This technique is used to convert data into certain codes, with the aim that the stored information cannot be read by anyone except those who have the right. In this study, a cryptography learning application was designed that implements encryption and decryption methods using the Vigenere cipher method. The results of the study are a cryptography learning application using the Vigenere cipher method that can encode secret messages and also help increase the understanding of users who want to learn about cryptography, especially the Vigenere cipher method.